2012
DOI: 10.1128/jcm.06587-11
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Human Papillomavirus (hrHPV) E6/E7 mRNA Testing by PreTect HPV-Proofer for Detection of Cervical High-Grade Intraepithelial Neoplasia and Cancer among hrHPV DNA-Positive Women with Normal Cytology

Abstract: T o reduce the mortality and morbidity of cervical cancer, most developed countries have adopted some form of cervical screening using cytological examination of cervical smears. However, cervical cytology is known to display only a modest sensitivity for cervical precancer or cancer (i.e., cervical intraepithelial neoplasia grade 2 or higher [ՆCIN2]) (3, 15).Infection with high-risk human papillomavirus (hrHPV) has been recognized as the necessary cause of cervical cancer (27,44). Recently, evidence has accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…[46][47][48] In conclusion, adding VIA to HPV testing improves PPV of cervical cancer screening, but at the cost of an important loss of sensitivity. Further studies are warranted to explore this strategy.…”
Section: Discussionmentioning
confidence: 89%
“…[46][47][48] In conclusion, adding VIA to HPV testing improves PPV of cervical cancer screening, but at the cost of an important loss of sensitivity. Further studies are warranted to explore this strategy.…”
Section: Discussionmentioning
confidence: 89%
“…The molecular detection of HPV provides evidence of the infection and Rijkaart et al (2012) demonstrated the risk of cervical intraepithelial neoplasia grade 2 or higher (≥CIN2) in 55% of women with positive expression of E6/E7 mRNA, HPV DNA with high positive oncogenic risk and normal oncotic cytologies, compared with 20% in those with negative test results. The authors concluded that the test could aid in the selection of women with high-oncogenic risk HPV for prompt referral or a colposcopic examination.…”
Section: Discussionmentioning
confidence: 99%
“…It has to be considered that despite normal cytology, women positive for high-risk HPV genotypes have much higher risk of developing CIN3+ in the future (33) . It has been recently shown among cytologically normal women, those testing E6/E7 mRNA positive were at a much higher risk for CIN2+ development comparing to mRNA negative, on a short follow-up period within 3 years (34) . NILM subjects harboring HPV 16 DNA may represent, in a subset, limitations of the cytological diagnosis.…”
Section: Discussionmentioning
confidence: 99%